Orders of Signification and Elements of Mythology of Educational Quotes - Rovita Jayaning Shoimmah; Rohmani Nur Indah (RETORIKA: Jurnal Ilmu Bahasa, 2021)
Quote in education, expanding positive messages aimed at everyone in achieving success that can be considered a social perspective. Education quotes consist of verbal and non-verbal elements to deliver messages in communication. Quotes play an important part in social communication, including analyzing and interpreting messages communicated with nonverbal meaning. There are two purposes of study in this study. This study aims to determine the significant meaning of the educational quotation at Quotefancy.com and to know the mythology elements found in the educational quotation at Quotefancy.com. This research is qualitative descriptive research in content analysis. This means that it does not require a statistical approach to investigating the data. Researchers use Roland Barthes's theory in semiotics to know the meaning of the educational quotation in analyzing data. By analyzing the data, there are two findings of this study. The first findings show two commands to investigate the meaning, which is domestic and connotative meaning. This study's second findings reveal that mythology in educational quotes is analyzed on verbal and non-verbal elements in each image.